Global Changes in 20‐Year, 50‐Year, and 100‐Year River Floods. Issue 6 (18th March 2021) - Slater, L.; Villarini, G.; Archfield, S.; Faulkner, D.; Lamb, R.; Khouakhi, A.; Yin, J.
Abstract: Concepts like the 100‐year flood event can be misleading if they are not updated to reflect significant changes over time. Here, we model observed annual maximum daily streamflow using a nonstationary approach to provide the first global picture of changes in: (a) the magnitudes of the 20‐, 50‐, and 100‐year floods (i.e., flows of a given exceedance probability in each year ); (b) the return periods of the 20‐, 50‐, and 100‐year floods, as assessed in 1970 (i.e., flows of a fixed magnitude ); and (c) corresponding flood probabilities. Empirically, we find the 20‐/50‐year floods have mostly increased in temperate climate zones, but decreased in arid, tropical, polar, and cold zones. In contrast, 100‐year floods have mostly decreased in arid/temperate zones and exhibit mixed trends in cold zones, but results are influenced by the small number of stations with long records, and highlight the need for continued updating of hazard assessments. Plain Language Summary: Here, we provide the first global examination of recent changes in the size, frequency, and probability of extreme river floods using historical river records. Since the 1970s, the 20‐year and 50‐year extreme river floods have mostly increased in temperate zones but decreased in arid, tropical, polar, and cold zones. In contrast, the 100‐year floods have decreased in arid and temperate zones, and show mixed results in cold zones, but at a smaller sample of sites with long records. Descriptions of changes in extreme flooding depend largely on site selection, and are constrained by availability of long‐term data. Overall, our findings highlight the importance of regularly updating flood hazard assessments under nonstationarity. Key Points: We provide the first global nonstationary assessment of changes in the magnitude, return period, and probability of observed extreme floods We find increasing 20‐year and 50‐year floods in temperate climate zones but mostly decreases in arid, tropical, polar, and cold zones For the 100‐year floods, at a smaller sample of sites, we find decreases in arid and temperate zones and mixed results elsewhere